Rancangan Pembukaan Wilayah Hutan pada Areal Hutan Tanaman Rakyat di Kelompok Tani Hutan Tunas Harapan Desa Cenrana Kecamatan Camba Kabupaten Maros - abdul hakim (Jurnal Eboni, 2021)
This research was conducted at Cenrana village, Camba subregency, Maros regency. the researchaims to compose the planning of the forest area clearance as participation at the forest acreage ofpeople’s plant of the Tunas Harapan farmer’s group at Cenrana village, Camba sub regency, Marosregency. This research was hopefully useful as an input for the Tunas Harapan farmer’s group in theimplementation of the people’s plant forest development which they managed. The data collecting weredone by the field observation and mapping by using GPS to collect primary data. The investigationcovered kinds of plants and the planting pattern which was used by the farmer group members, facilitiesand infrastructures which existed around the forest acreage of people’s plant. the results indicate thatthe large area of HTR Tunas Harapan will be managed are 28 Ha, and each farmer will manage 2,8 Ha.The infrastructures in that area are village road with 6,5 km long and 3-4 m wide, orchard road 1,6 kmlong with 3 m wide, kampong road 3 km long and 1-3 m wide, and footpath road 300 m long and 1 mwide. There are 3 road classes which will be used, namely, 1) orchard road (class 1) will be used as themain road, 2)kampong road (class 2), and 3) footpath (class 3). The planning pattern will be used fromthe first year to the third year is the agroforestry pattern and in the fourth year will be theagrosilvopasture pattern.